KINERJA DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA DALAM PEMBERANTASAN BUTA AKSARA DI KABUPATEN MINAHASA SELATAN PROVINSI SULAWESI UTARA - Kasenda, Rivan; Pombengi, Jericho; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2016)
The purpose of this study was to determine the extent of Performance Department of Education Youth andSports in the eradication of illiteracy in the South Minahasa district. In this study, the authors use the theory of theperformance of public organizations of Agus Dwiyanto, where the indicator of productivity, quality of service,responsiveness, responsibility and accountability on the performance Dikpora in the eradication of illiteracy in theSouth Minahasa district. Productivity of employees in carrying out the task of public service within the meaning ofserving the eradication of illiteracy are not yet optimal. Quality of service is not their complaint or a suggestion boxfacility if people are not satisfied with the services provided. Because customer satisfaction is the extent to which thenotion of performance of products or services meet the expectations of society. Responsiveness is lacking so that theresponsiveness Dikpora in accommodating and following up aspirations of the community, especially in combatingilliteracy. Responsibility performance is no longer entering literacy programs into the annual performance planDikpora South Minahasa district, because the organization would achieve the stated goals when performance is inaccordance with the predetermined plan that is from the beginning of the work. While the accountability of theDepartment of Education, Youth and Sports in the eradication of illiteracy is a form of accountability for serviceproviders literacy to all parties who have the right and authority to hold accountable those either directly orindirectly.This study uses qualitative research methods and retrieve information through interviews with eightinformants and assisted with interview guides available. It was concluded that the South Minahasa District Dikporaperformance in the eradication of illiteracy has not run optimally.Keywords: organizational performance, the eradication of illiteracy